Is there still an added-worker effect? - Chinhui Juhn; Simon Potter (Federal Reserve Bank of New York, 2007)
Using matched March Current Population Surveys, we examine labor market transitions of husbands and wives. We find that the “added-worker effect”—the greater propensity of nonparticipating wives to enter the labor force when their husbands exit employment— is still important among a subset of couples, but that the overall value of marriage as a risk-sharing arrangement has diminished because of the greater positive co-movement of employment within couples. While positive assortative matching on education did increase over time, this shift in the composition of couple types alone cannot account for the increased positive correlation.
Keywords: J0; E2; C1; 330; labor; married; Bayesian; participation; Ehe; Beschäftigung; Weibliche Arbeitskräfte; Arbeitsangebot; Frauen; Arbeitslosigkeit; Männer; Schätzung; USA